Overcoming climate change challenges: The role of irrigation in enhancing rice yield in Tanzania - Peter David Kulyakwave; Yu Wen; Xu Shiwei (Economics, Management and Sustainability)
Rural farmers face different challenges from climate change and weather variability, which have threatened crop production and productivity. Small-scale farmers try to cope with the prevailing situations by adjusting to different mechanisms, including adopting irrigation services. This study seeks to determine factors influencing rice farmers' decision to adopt irrigation technology and determine the significant contribution of irrigation to rice yields in the Mbeya Region of Tanzania. Data was collected through structured questionnaires, interviews, and focus discussions. Descriptive statistics, Logistic regression, and Ordinary Least Square regression by Stata software performed data analyses. The descriptive statistics characterized households' socio-demographic and economic characteristics. Logistic regression results affirmed that households' education, labor size, meteorological information, access to financial services, extension services, and previous farm outputs significantly influenced irrigation adoption by farmers. Ordinary Least Square regression results confirmed that irrigation significantly contributed to rice yield at P>0.05 level. The study recommends adopting irrigation technology in Tanzania as a coping strategy for the negative impact of climate change and weather variations.